2018
DOI: 10.1111/ajt.14464
|View full text |Cite
|
Sign up to set email alerts
|

Harms of unsuccessful donation after circulatory death: An exploratory study

Abstract: While donation after circulatory death (DCD) has expanded options for organ donation, many who wish to donate are still unable to do so. We conducted face-to-face interviews with family members (N = 15) who had direct experience with unsuccessful DCD and 5 focus groups with professionals involved in the donation process. We used qualitative content analysis to characterize the harms of nondonation as perceived by participants. Participants reported a broad spectrum of harms affecting organ recipients, donors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…ethical debates) and were excluded from the present review, leaving 119 sources. While writing up the review, a relevant article was published ( Taylor et al, 2017 ), and this was added giving a total of 120 sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ethical debates) and were excluded from the present review, leaving 119 sources. While writing up the review, a relevant article was published ( Taylor et al, 2017 ), and this was added giving a total of 120 sources.…”
Section: Resultsmentioning
confidence: 99%
“…Many families reconcile features of the experience by concluding that life without brain function is not the life they want for their relative ( Long et al, 2006 ) and some consent to donation hoping that the delay between consent and surgery would provide one last chance for recovery ( Manuel et al, 2010 ; Rassin et al, 2005 ). Knowing the time of death is important to families ( Fulton et al, 1977 ; Holtkamp, 1997 ; Northam, 2015 ), and Taylor et al (2017) found that when families had consented to donation after cardiac death (DCD) and their relative did not die within the required timeframe, some family members questioned whether they had given up too soon.…”
Section: The Family Bereavement Experiencementioning
confidence: 99%
“…An American study found that unsuccessful DCD was associated with a broad spectrum of harms as experienced by family members and confirmed by professionals who cared for them. Despite these harms, many families did not regret attempted donation …”
Section: Case Analysis and Discussionmentioning
confidence: 99%
“…This perception is consistent with results from interviews with donor families. 32,33 Participants in the present study considered care of the patient and family an overriding priority and only saw donation as a positive outcome if it was consistent with patient values and preferences. This is a novel observation, but has been hinted at in existing research.…”
Section: Suggested Practices Align With Those Reported Elsewherementioning
confidence: 99%